Usefulness of on‐site cytology of liver tumor biopsy in specimen sampling for cancer genomic profiling test. (11th January 2023) - Nakabori, Tasuku; Abe, Yutaro; Higashi, Sena; Mukai, Kaori; Yoshioka, Risa; Morimoto, Yuki; Koyanagi, Yuki; Tanada, Satoshi; Nagata, Shigenori; Honma, Keiichiro; Ohkawa, Kazuyoshi
Abstract: Aim: Appropriate sample selection with a tumor fraction ≥20% without necrosis contamination is required for successful cancer genomic profiling (CGP). Rapid on‐site evaluation (ROSE) is performed to assess adequate sampling. Method: This retrospective study included 54 patients who underwent CGP using liver tumor biopsy specimen with ROSE. Result: The sampling success rate (98.1%) was higher than the previously reported 77.5%–88.9%. ROSE was performed once in 51 patients and twice in three patients; for those undergoing ROSE twice, the first ROSE was negative for malignancy, or showed few tumor cells with necrotic cell contamination, while the second ROSE obtained from another location showed abundant malignant cells. In these patients, the CGP was successful using the second specimen, though the first sample did not meet the required criteria for CGP test. Conclusion: Performing ROSE during liver tumor biopsy may be useful for CGP test sampling because ROSE prevents sampling errors and contributes to adequate sampling. Abstract : ROSE prevents sampling errors and contributes to adequate sampling for cancer genomic profiling test. ROSE could possibly predict the quality of biopsied specimens. Performing ROSE during liver tumor biopsy may be useful in collecting specimens for the CGP test, although considerable effort is required by cytotechnologists and cytopathologists.